2016
DOI: 10.1002/jsfa.7790
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofPrunus mumeSieb. et Zucc. extract and its biopolymer encapsulation on a mouse model of colitis

Abstract: These results indicated that the effects of the PM extract on colitis were not influenced by biopolymer encapsulation and that this PM extract could be a potential therapeutic agent for inflammatory bowel disease. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Some studies have assessed further beneficial effects of P. mume extract or formulation on different IBD mouse models. The results showed that P. mume treatment decreased immunoglobulin M (IgM) and immunoglobulin E (IgE) levels, reduced COX-2, tumor necrosis factor alpha (TNF-α), interferon (IFN-γ), interleukin (IL)-12, and IL-17 levels in the colon tissue of colitis mouse models, alleviated dextran sulfate sodium (DSS) or 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced histological changes and inflammatory responses (Liu et al, 2009;Zhang et al, 2011;Lee et al, 2014;Lee S. Y. et al, 2017;Kim et al, 2021). All these studies show that P. mume may represent a potential new therapeutic agent for IBD treatment.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Some studies have assessed further beneficial effects of P. mume extract or formulation on different IBD mouse models. The results showed that P. mume treatment decreased immunoglobulin M (IgM) and immunoglobulin E (IgE) levels, reduced COX-2, tumor necrosis factor alpha (TNF-α), interferon (IFN-γ), interleukin (IL)-12, and IL-17 levels in the colon tissue of colitis mouse models, alleviated dextran sulfate sodium (DSS) or 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced histological changes and inflammatory responses (Liu et al, 2009;Zhang et al, 2011;Lee et al, 2014;Lee S. Y. et al, 2017;Kim et al, 2021). All these studies show that P. mume may represent a potential new therapeutic agent for IBD treatment.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…In a rat model of chronic cerebral hypoperfusion, the ethanol extract of Prunus mume ameliorated neurological dysfunction by inhibition of pro-inflammatory cytokines [12]. Further, Lee et al (2017) [13] reported that Prunus mume extract showed an anti-colitis effect on DSS-induced colitis mice. However, the effect of LAB-fermented Prunus mume juice (PJ) to improve the features of colitis in mice needs to be explored.…”
Section: Introductionmentioning
confidence: 96%
“…The inhibitory effects of Prunus mume on intestinal inflammation have been reported for a decade. The Prunus mume extract decreased pro-inflammatory cytokines, which showed high radical scavenging and superoxide dismutase-like activities [11]. In a rat model of chronic cerebral hypoperfusion, the ethanol extract of Prunus mume ameliorated neurological dysfunction by inhibition of pro-inflammatory cytokines [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 It has also been shown to possess a wide variety of other beneficial effects, including anticancer, [9][10][11][12] anti-microbial, 13 anti-inflammatory, 14,15 antioxidant, 16,17 anti-fatigue, 18 antiviral, 19,20 and other bioactivities properties. [21][22][23][24][25][26][27] According to the World Health Organization (WHO), cancer has become the second leading cause of death after cardiovascular and cerebrovascular diseases. 28 However, most chemosynthetic anticancer drugs have great toxicity and pose side effects to normal human cells.…”
Section: Introductionmentioning
confidence: 99%